Evaluación de calidad de la atención farmacéutica en hospitales públicos y farmacias privadas de Machala, Ecuador. - Raza Chamorro, Melanie Aidée; Salcedo Aguilar, Cristina Geraldy (My University, 2025)
Introduction: Pharmaceutical care is essential to ensure the proper use of medications, as it allows for the identification, prevention, and resolution of potential problems, thus strengthening the quality of care in both public and private pharmacies. Objective: To evaluate patient perceptions and satisfaction with the pharmaceutical care received in hospitals and private pharmacies in Machala, Ecuador, identifying specific strengths and areas for improvement in each sector. Methodology: The research was descriptive, non-experimental, and qualitative. It was conducted in hospital and community pharmacies in Machala, Ecuador. Surveys based on the SERVQUAL model were administered to patients and clients who visited these establishments between March and April 2025, in order to determine their perceptions and satisfaction with the pharmaceutical care received. The data collected were statistically analyzed using Jamovi software version 2.6.22. Results: The results show that in the public sector, the majority of users (79.6%) are satisfied with pharmaceutical care, although only 17.8% consider it very satisfactory. In contrast, in the private sector, the perception of being very satisfied predominates (63.9%), reflecting a more positive assessment of the quality received. These data highlight the need to strengthen key aspects such as personalized care, infrastructure, and patient orientation, especially in the public sector, to achieve a service that not only meets expectations but also generates trust and complete satisfaction. Conclusions: Strengths were highlighted in the humanistic approach of the public sector and in the infrastructure of the private sector, although areas for improvement were identified in technology and process standardization. Trust and quality of care are key for both sectors.
Introducción: La atención farmacéutica es esencial para garantizar el uso adecuado de los medicamentos, ya que permite identificar, prevenir y resolver posibles problemas, fortaleciendo así la calidad de la atención tanto en farmacias públicas como privadas. Objetivo: Evaluar la percepción y satisfacción de los pacientes con respecto a la atención farmacéutica recibida en hospitales y farmacias privadas de Machala, Ecuador, identificando fortalezas y áreas de mejora específicas en cada sector. Metodología: La investigación fue de tipo descriptivo, no experimental y con enfoque cualitativo, y se realizó en farmacias hospitalarias y comunitarias de Machala, Ecuador. Se aplicaron encuestas basadas en el modelo SERVQUAL a pacientes y clientes que acudieron a estos establecimientos entre el periodo de marzo y abril del 2025, con el fin de conocer su percepción y satisfacción respecto a la atención farmacéutica recibida. Los datos recolectados se analizaron estadísticamente mediante el software Jamovi versión 2.6.22. Resultados: Los resultados muestran que en el sector público la mayoría de usuarios (79,6 %) se encuentra satisfechos con la atención farmacéutica, aunque solo un 17,8 % la considera muy satisfactoria. En cambio, en el sector privado predomina la percepción de muy satisfecho (63,9 %), lo que refleja una valoración más positiva de la calidad recibida. Estos datos evidencian la necesidad de reforzar aspectos clave como la atención personalizada, la infraestructura y la orientación al paciente, especialmente en el ámbito público, para lograr un servicio que no solo cumpla expectativas, sino que genere confianza y satisfacción plena. Conclusiones: Se destacaron fortalezas en el trato humanístico del sector público y en la infraestructura del privado, aunque se identificaron áreas de mejora en tecnología y estandarización de procesos; la confianza y calidad en la atención resultan claves para ambos sectores.
Keywords: ATENCIÓN FARMACÉUTICA; FARMACIA; SATISFACCIÓN; PERCEPCIÓN